Podstawowe przesłanki handlowej obsługi przemysłu - Sławińska, Maria (Wydział Prawa i Administracji UAM, 1975)
Commercial service to industry is expressed in two ways : through direct service to the manufacturer and through cooperation of trade with industry. The purpose of the article is to present the conditions which describe the role of trade in the disposal of industrial products in the supply of material technology. Among the basic conditions of commercial service to industry the following are included: 1) social division of labor, 2) the occurrence of divergence between the sphere of production and the sphere of consumption and wear, 3) the system of planning and running the economy along with the structure of the national economy, 4) the possibilities of better recognition of demand through trade, 5) the necessity of assuring the effectiveness of the supply process of material technology. The first two are fundamental and objective, pointing out the need for the existence of commercial service to industry. Industry with reference to most products, is not able to bring into accordance the commodities offered with that of demand in a cross-section by type, quantity, time, space and assortment, especially in reference to consumptive goods and those means of production which are produced to supply numerous consumers and are procured by them in relatively small amounts. However, the remaining conditions, depending upon the existing eco-organizational and lawful solutions, as well as the economic situation, define the realm of commercial service to industry.
Basic Conditions of Commercial Service to Industry